Affective neuroscience: a primer with implications for forensic psychology - Grimshaw, Gina M. (Psychology, crime & law, 2018)
Emotions have important implications for many aspects of cognition and behaviour, including those that are of concern to forensic psychologists. This review article provides an overview of the emerging field of affective neuroscience - the scientific discipline that seeks to identify the neural mechanisms that give rise to emotion. The theories and methods in the field are described, and then applied to emotional states and issues that are relevant in forensic contexts, including fear and anxiety, anger and aggression, pleasure and reward, empathy, emotion regulation, and emotional memory. The review concludes with a summary of the uses (and misuses) of affective neuroscientific research, and the potential for future applications of this knowledge.